(untitled) (Global Journal of Human-Social Science, 2015)
The present study attempts an analysis of the first inaugural address of President Abdel Fatah El-Sisi. It aims at exploring the persuasive strategies used by President El-Sisi in his address. It also attempts to investigate the use of linguistic strategies in this type of Arabic political discourse. The study applies Aristotle’s model for investigating persuasion. It also draws on work from Atkinson’s (1984) linguistic strategies and Charteris-Black’s (2014) persuasion theory. Results of the study showed that El-Sisi’s first inaugural address was successful due to the use of certain rhetorical and linguistic strategies. The analysis indicated that the address has four effectively employed parts, namely, the prologue, the narrative, the proof, and the epilogue. Results also showed that the use of the artistic proofs in the address as a whole is similar to that identified by Aristotle. However, the analysis demonstrated the use of two novel usages that are successfully manipulated in the address.